PERAN KEPEMIMPINAN DI LEMBAGA PENDIDIKAN ISLAM - Bashori, Bashori; Chaniago, Zeni Isnina; Oktaviani, Melati; Tamin, Berliana (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2020)
Leadership is the ability and readiness of a person to be able to influence, encourage, invite, guide, move others in order to help achieve certain goals. Leadership is essentially related to organized human labor, and as a power or potential. The purpose of this study aims to describe and analyze the role of leadership in Islamic educational institutions. This research method uses a library research approach (library research). The results of this study indicate that the leadership function is; 1) Instruction function; 2) Consultation function; 3) Participation function; 4) Delegation function; and 5) control function. The role of the leader is; a) Future leaders must be flexible and have extensive experience; b) As head of the organization, it becomes a necessary function, not something trivial that must be delegated to others; and c) Policy making is no longer effective at the top of the organization.